WACANA AMANDEMEN KELIMA UNDANG-UNDANG DASAR 1945 SEBAGAI LANGKAH MEWUJUDKAN ARSITEKTUR KONSTITUSI DEMOKRATIK - Mohammad Maiwan (Program Studi PPKn FIS UNJ & Asosiasi Profesi PPKn Indonesia, 2013)
The amendment of constitution is something commonly done and is part of the practice of national life. In Indonesian society there is some perspectives of the fifth constitution amendment. The first, is a group that wants the fourt constitution amendment retained. Secondly, a group that wants the amendment of the constitution. Third, is the group that want to go back to the original 1945 constitution. However, the amendment must be conducted in-depth, thorough, consistent, integrated, thus strengthening the Indonesian constitutional system. The main aspect that should be emphasized is to restore sovereignty to the people through the implementation of participatory democracy and good governance.